Effect of Advance Care Planning on Heart Failure Patients: An Evidence Based Case Report - Shatri, Hamzah; Nurfitria, Nandika; Sinulingga, Dika; Irvianita, Vinandia; Faisal, Edward; Putranto, Rudi; Martina, Diah (UI Scholars Hub, 2022)
Despite the advances in medical therapy, heart failure remains a disease that requires attention due to the course of the illness; it can lead to unpredictable, progressive, and fatal conditions. Existing therapy aims to improve the condition and prevent disease progression, with a balanced secondary therapy for various conditions that can trigger acute decompensated heart failure. Advances in technology and therapy may increase the prevalence of patients with heart failure, including prolonging the refractory phase of the disease. There are recommendations for advance care planning to support patient therapy and improve the quality of life of patients with heart failure. This evidence-based case report aims to investigate the benefits of advance care planning in heart failure patients. A heart failure patient is referred to the palliative care team for advance care planning. Literature searches were conducted on ProQuest, PubMed, Scopus, and Cochrane according to the clinical questions. The studies were selected based on the inclusion and exclusion criteria, then a critical review was conducted. One study showed significant results regarding the effectiveness of advance care planning on the quality of life of heart failure patients. Another study showed a significant improvement in depression among patients engaged in advance care planning. However, it showed no difference in the quality of life compared to usual care because the sample size was relatively small, and the quality of evidence was low. Therefore, it can be concluded that advance care planning can improve heart failure patients’ psychological symptoms and quality of life.